Flow and diffusion around and within diatom aggregates: Effects of aggregate composition and shape. (13th February 2020) - Zetsche, Eva‐Maria; Larsson, Ann I.; Iversen, Morten H.; Ploug, Helle
Abstract: Diatom aggregates constitute a significant fraction of the particle flux from the euphotic zone into the mesopelagic ocean as part of the ocean's biological carbon pump. Modeling studies of their exchange processes with the surrounding water usually assume spherical shape and that aggregates are impermeable to flow. Using particle image velocimetry, we examined flow distributions around individual aggregates of various irregular shapes formed from two different diatom species: (1) Skeletonema marinoi, known for its cell–cell stickiness, and (2) Chaetoceros affinis, exhibiting cell‐TEP (transparent exopolymeric particles) stickiness. Chaetoceros aggregates formed porous, highly irregularly shaped aggregates as compared to the more compact and near‐spherical Skeletonema aggregates, yet flow distributions around both types of aggregates were relatively similar at a millimeter scale. At a micrometer scale, the irregular shape of diatom aggregates caused velocity gradients and vorticity close to the surface to locally vary more than for spherical model aggregates (agar‐yeast spheres). Water was deflected from the surface of all aggregate types and we found no direct evidence that flow occurred within aggregates. Digital holographic imaging and Alcian blue staining revealed a substantial presence of TEP likely clogging the interstitial pore spaces in Chaetoceros aggregates. Radial oxygen concentration distributions measured by O2 microsensors within the aggregates were similar to those modeled for aggregates and spheres impermeable to flow. Thus, transport of gases, nutrients, and solutes likely occurs by diffusion, even within large, irregularly shaped diatom aggregates during sinking.